Pemberdayaan Ekonomi Keluarga Melalui Strategi Literasi Keuangan Partisipatif Bagi Ibu Rumah Tangga - Muliani Mangngalla (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
This community service activity aims to enhance the understanding and financial management skills of housewives to strengthen domestic economic resilience in Marrang Village. The program was implemented using participatory socialization, interactive discussions, and real-life simulations focusing on daily expense recording techniques, prioritizing needs over wants, and strategies for emergency fund allocation. The results of the activity showed that the 10 participants exhibited very high enthusiasm, along with a significant escalation in financial literacy and managerial awareness, as evidenced by evaluation results. Based on post-test data, the participants' average understanding of financial recording increased sharply from 40% in the pre-test to 100% after the activity, while the ability to allocate income based on priority reached 90%. Furthermore, participants demonstrated a new commitment to implementing disciplined saving as a foundation for family financial security. In general, this activity provided a constructive impact in shifting consumptive behavior toward a planned-productive pattern. These findings indicate that practice-based financial education is crucial for rural households. Follow-up programs such as periodic mentoring through community groups and the development of simple recording media are recommended to ensure the systematic sustainability of healthy financial habits.